1998
DOI: 10.1046/j.1365-2842.1998.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Curing depth of a composite veneering material polymerized with seven different laboratory photo‐curing units

Abstract: Properties of laboratory-cured composite materials are affected by the type of activation system as well as by the photo-curing unit light source. This study examined curing depth of a composite veneering material polymerized by means of various photo-curing units with the aim of evaluating the curing performance of the light sources. A microfilled composite material designed for prosthetic veneer was cured with seven photo-curing units. The light sources of the units were halogen/fluorescent, xenon, metal hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 16 publications
1
38
0
3
Order By: Relevance
“…For both materials, polymerization with Hyper LII -which had the highest light intensity-resulted in the lowest wear; conversely, polymerization with Labolight LV-II resulted in the highest wear. Results obtained in this study agreed with previous reports in that wear-resistant materials showed excellent mechanical properties 8,13,15) , and that the mechanical properties and wear resistance of light-polymerized composite materials could be considerably improved by application of high-intensity light sources 17,28,29) . Apart from the effect of high-intensity light sources, we speculated that improvement in the double bond conversion of monomers in the composite matrix played a role in improving the wear resistance and properties of composite materials.…”
Section: Factors Which Influence the Wear Of Indirect Compositessupporting
confidence: 91%
See 2 more Smart Citations
“…For both materials, polymerization with Hyper LII -which had the highest light intensity-resulted in the lowest wear; conversely, polymerization with Labolight LV-II resulted in the highest wear. Results obtained in this study agreed with previous reports in that wear-resistant materials showed excellent mechanical properties 8,13,15) , and that the mechanical properties and wear resistance of light-polymerized composite materials could be considerably improved by application of high-intensity light sources 17,28,29) . Apart from the effect of high-intensity light sources, we speculated that improvement in the double bond conversion of monomers in the composite matrix played a role in improving the wear resistance and properties of composite materials.…”
Section: Factors Which Influence the Wear Of Indirect Compositessupporting
confidence: 91%
“…For Hyper LII unit (Toho Dental Products, Saitama, Japan) 28) , two metal halide lamps were used for the light source; for -Light II unit (J. Morita Corp., Suita, Japan) 29) , a halogen lamp and two fluorescent tubes were used; for Labolight LV-II unit (GC Corp.) 29) , three fluorescent tubes were used. Table 1 summarizes the details concerning the composite materials, casting alloy, and polymerization units.…”
Section: Materials and Polymerization Unitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a metal halide lamp that emits both ultraviolet and visible light is one of the new extra-oral light sources with high lightintensity. The effectiveness of the metal halide unit in polymerization of light-activated material has been Depth of cure and hardness of an indirect composite polymerized with three laboratory curing units Naomi Tanoue 1) , Mahoko Murakami 2) , Hiroyasu Koizumi 3,4) , Mitsuru Atsuta 5) and Hideo Matsumura Original demonstrated by many researchers (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Tanoue et al (9) examined certain properties of indirect composites polymerized with different light sources, and reported that hardness and water solubility were strongly influenced by the type of laboratory light-polymerizing units. The role of the laboratory light-polymerizing unit has also been indicated for improvement of curing depth and wear resistance (5,10).…”
Section: Introductionmentioning
confidence: 99%